Feeding ecology of Auchenipterichthys longimanus (Siluriformes: Auchenipteridae) in a riparian flooded forest of Eastern Amazonia, Brazil - FREITAS, Tiago Magalhães da Silva (2014)
Feeding habits of the midnight catfish Auchenipterichthys longimanus collected in rivers of the Caxiuanã National Forest (Eastern Amazonia, Brazil) were investigated through the different hydrological periods (dry, filing, flood and drawdown). A total of 589 specimens were collected throughout seven samplings between July 2008 and July 2009, of which 74 were young males, 177 adult males, 89 young females and 249 adult females. The diet composition (Alimentary index – Ai%) was analyzed by a non-metric multidimensional scaling (nMDS) and by the analysis of similarity (ANOSIM), which included 37 items grouped into nine categories (Aquatic insects, Other aquatic invertebrates, Arthropods fragment, Fish, Plant fragment, Seeds, Terrestrial insects, Other terrestrial invertebrates, and Terrestrial vertebrates). We also calculated the niche breadth (Levins index) and the repletion index (RI%). Differences in the diet composition between hydrological seasons were registered, primarily on diet composition between dry and flood season, but changes related with sex and maturity were not observed. The midnight catfish showed more specialists feeder habit in the flood period (March 2009) and more generalist habits in the dry season (November 2008). The amount of food eaten by A. longimanus based on repletion index (RI%), did not differ significantly from sex and maturity. However, we evidenced differences in RI% when comparing the studied months. These results provide important biological information about the trophic ecology of auchenipterids fish. In view of the higher occurrence of allochthonous items, this research also underpins the importance of riparian forests as critical environments in the maintenance and conservation of wild populations of fish in the Amazon basin.